Od „Hiszpanii imperialnej” do „imperium europejskiego”. Fundamentalne koncepcje ideowo-polityczne hiszpańskich narodowych rewolucjonistów przełomu XX i XXI w. Część I. Nacjonaliści hiszpańscy - Karczewski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article presents the system of fundamental principles and ideas promulgated by contemporary Spanish national-and-revolutionary parties. These organizations, from an ideological standpoint, can be placed within a general European doctrinal movement, which came into existence during the sixties of the 20th century, called tercerism, the Third Way, the Third Position or revolutionary Nationalism. Spanish national-and-revolutionary parties base their conceptions on an outlook affirming modernity reason, science, progress and consider ancient civilizations of Greece and Rome the source of European identity. From the perspective of the system of ideas we can divide these parties into two groups, the first one being in favor of Spanish Nationalism Spanish nation as the highest value in the axiological system and the second one advocating European Nationalism the postulate of and the hope for the establishment of the new European nation and of the new European government. The article has been divided into two parts, respectively describing these ideological currents. In case of the parties supporting “Spanish Nationalism” the system of ideas is based on two pillars: Spanish peoples regions and the Spanish nation. Spanish peoples, meaning traditional regions, are conceptualized as cultural and linguistic communities; their foundation is of a spiritual nature. In turn, the Spanish nation is understood as an organic whole, community of various and diverse Spanish peoples regions, arising on the basis of shared blood in the historical process the ethnic connection, in case of some organizations also a racial one, brought and kept together by tradition the essence of which is a feeling of a universal mission of integration, of “the project of the future” inherently encompassing the imperial idea.
Keywords: Hiszpania; nacjonalizm; terceryzm; doktryny polityczne